Alpha-defensins 1-3 release by dendritic cells is reduced by estrogen - Sperling Rhoda; Rodríguez-García Marta; Escribese Maria M; Engel Stephanie M; Gallart Teresa; Moran Thomas M (BMC, 2011)
Abstract Background During pregnancy the immune system of the mother must protect any activation that may negatively affect the fetus. Changes in susceptibility to infection as well as resolution of some autoimmune disorders represent empirical evidence for pregnancy related alterations in immunity. Sex hormones reach extremely high levels during pregnancy and have been shown to have direct effects on many immune functions including the antiviral response of dendritic cells. Among the immunologically active proteins secreted by monocyte derived DCs (MDDC) are the alpha-defensins 1-3. This family of cationic antimicrobial peptides has a broad spectrum of microbicidal activity and has also been shown to link innate to adaptive immunity by attracting T cells and immature DCs, which are essential for initiating and polarizing the immune response. Methods We compare culture-generated monocyte derived DCs (MDDCs) with directly isolated myeloid dendritic cells (mDCs) and plasmacytoid dendritic cells (pDCs) and measure their alpha-defensins 1-3 secretion by ELISA both, in basal situations and after hormone (E2 or PG) treatments. Moreover, using a cohort of pregnant women we isolated mDCs from blood and also measure the levels of these anti-microbial peptides along pregnancy. Results We show that mDCs and pDCs constitutively produce alpha-defensins 1-3 and at much higher levels than MDDCs. Alpha-defensins 1-3 production from mDCs and MDDCs but not pDCs is inhibited by E2. PG does not affect alpha-defensins 1-3 in any of the populations. Moreover, alpha-defensins 1-3 production by mDCs was reduced in the later stages of pregnancy in 40% of the patients. Conclusions Here, we demonstrate that mDCs and pDCs secrete alpha-defensins 1-3 and present a novel effect of E2 on the secretion of alpha-defensins 1-3 by dendritic cells.